Osteoarthritis in older adults: A global health challenge and the role of high BMI in shaping disease trends - Yan Gao; Hailong Yu; Wenfeng Han; Ning Wang; Bin Zheng; Aoxiang Yang; Yu Wang (PLoS ONE, 2026)
Background This study aimed to estimate the global, regional, and national Osteoarthritis (OA) burden and trends in older adults from 1990 to 2021, with a particular focus on the contribution of high body mass index (BMI) to the OA burden. Methods Using 2021 Global Burden of Disease Study data, we estimated the incidence, DALYs, and trends of OA in older adults across 204 countries and territories from 1990 to 2021. Spearman’s correlation analysis was applied to investigate relationships between age-standardized rates and the sociodemographic index (SDI). We quantified the BMI-attributable contribution to the OA burden. The Bayesian Age-Period-Cohort (BAPC) model was applied to project the global OA trend in older adults up to 2040. Results From 1990 to 2021, global OA cases in older adults increased by 148.65%. Age-standardized incidence and DALY rates increased annually by 0.08% and 0.31%, respectively. East and Southeast Asia exhibited the fastest increase in age-standardized DALY rates. The OA burden peaked in the 65–69-year age group, with women compared with men experiencing a higher burden. Knee OA imposed the heaviest burden, followed by hand OA, with regional variations across four anatomical sites. The OA burden, including specific sites, positively correlated with the SDI. The attributable proportion of OA burden due to high BMI increased by 21.39%, with the knee OA burden from high BMI exceeding the hip OA burden. The BAPC model predicted that OA burden will continue to rise in the future. Conclusions OA in older adults is a major global challenge, with knee OA being the most burdensome. High BMI, a modifiable risk factor, contributes significantly to OA, particularly in the knees. To reduce the OA burden, public health strategies should prioritize obesity prevention through weight management and awareness campaigns for older adults.